2018
DOI: 10.3390/molecules23030662
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Conjugating Enzyme Gene Family in Longan (Dimocarpus longan Lour.): Genome-Wide Identification and Gene Expression during Flower Induction and Abiotic Stress Responses

Abstract: Ubiquitin-conjugating enzymes (E2s or UBC enzymes) play vital roles in plant development and combat various biotic and abiotic stresses. Longan (Dimocarpus longan Lour.) is an important fruit tree in the subtropical region of Southeast Asia and Australia; however the characteristics of the UBC gene family in longan remain unknown. In this study, 40 D. longan UBC genes (DlUBCs), which were classified into 15 groups, were identified in the longan genome. An RNA-seq based analysis showed that DlUBCs showed distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…20 E2 enzymes have been found in Caenorhabditis elegans [77], 40 in A. thaliana [68], 14 in Saccharomyces cerevisiae [78], 37 in human [67], 48 in rice [79], 75 in maize [80], 72 in banana [81], 43 in Vitis vinifera [82], 34 in Carica papaya [83], 59 in tomato [84], 40 in Dimocarpus longan Lour. [85], and 57 in potato [86].…”
Section: The Family Of E2 Enzymesmentioning
confidence: 95%
See 1 more Smart Citation
“…20 E2 enzymes have been found in Caenorhabditis elegans [77], 40 in A. thaliana [68], 14 in Saccharomyces cerevisiae [78], 37 in human [67], 48 in rice [79], 75 in maize [80], 72 in banana [81], 43 in Vitis vinifera [82], 34 in Carica papaya [83], 59 in tomato [84], 40 in Dimocarpus longan Lour. [85], and 57 in potato [86].…”
Section: The Family Of E2 Enzymesmentioning
confidence: 95%
“…in Vitis vinifera [82], 34 in Carica papaya [83], 59 in tomato [84], 40 in Dimocarpus longan Lour. [85], and 57 in potato [86]. The ubiquitin E2 variant (UEV) is similar to the E2 enzyme in both sequence and structure, but it cannot form a thioester linkage with ubiquitin because of the lack of the catalytic cysteine residue [87,88].…”
Section: The Family Of E2 Enzymesmentioning
confidence: 99%
“…A total of 42 DlST genes underwent AS events in flower buds, with 38 genes in flower and 33 genes in pericarp, stem and young fruit; the AS events in pulp was the lowest (21) (Figure 7 and Table S2). By analyzing the transcriptome of nine tissues in 'Sijimi', we found that young fruit (143) and pulp (58) accounted for the largest and smallest number of AS events in DlST genes, respectively. Alternative 5 splice site (143) and skipped exon (58) was the most and least common, respectively.…”
Section: Alternative Splicing (As) Events Analysis Of Dlstsmentioning
confidence: 99%
“…By analyzing the transcriptome of nine tissues in 'Sijimi', we found that young fruit (143) and pulp (58) accounted for the largest and smallest number of AS events in DlST genes, respectively. Alternative 5 splice site (143) and skipped exon (58) was the most and least common, respectively. A total of 42 DlST genes underwent AS events in flower buds, with 38 genes in flower and 33 genes in pericarp, stem and young fruit; the AS events in pulp was the lowest (21) (Figure 7 and Table S2).…”
Section: Alternative Splicing (As) Events Analysis Of Dlstsmentioning
confidence: 99%
See 1 more Smart Citation